The effect of the rehabilitation program on fat density level in blood (LDL-HDL) for the insufficient arteries patients for the male (50-55) years old - Abdel sattar, Basil (Journal of Physical Education, 2012)
The study consists five chapters. The researcher start with the importance of the study in a lack of human movments because of the development in technology with poor body activity and body physiological function, and alsot recognize the effect of rehabilitation program with vary exercise to become fit and to proper the need of arteries patient.The problem of the study lies in the increase of fat obesity in arteries, walls, so the researcher prepare rehabilitation program include aerobic and respiratory exercise to reduce fat ratio and improre cardiac hygiene.The hypothesis of the study confirm a statistical differences between pre and post test for the benefit of rehabilitation program.The study has been done on six subject who suffer from insufficient arteries disease, the sample have done blood test for the fat ratio in specific laboratory.The researcher used experimental design for one month, three times a week, with (20-30) minutes for each training day.The researcher has been reach the following result that the rehabilitation program was positive inffuence on patients hygiene with reduce in fat ratio (high – low) level.The researcher recommended for yearly blood test to identify the fat density in blood and to observe patient body health .